If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7a(4a + -4) = 0 Reorder the terms: -7a(-4 + 4a) = 0 (-4 * -7a + 4a * -7a) = 0 (28a + -28a2) = 0 Solving 28a + -28a2 = 0 Solving for variable 'a'. Factor out the Greatest Common Factor (GCF), '28a'. 28a(1 + -1a) = 0 Ignore the factor 28.Subproblem 1
Set the factor 'a' equal to zero and attempt to solve: Simplifying a = 0 Solving a = 0 Move all terms containing a to the left, all other terms to the right. Simplifying a = 0Subproblem 2
Set the factor '(1 + -1a)' equal to zero and attempt to solve: Simplifying 1 + -1a = 0 Solving 1 + -1a = 0 Move all terms containing a to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1a = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1a = 0 + -1 -1a = 0 + -1 Combine like terms: 0 + -1 = -1 -1a = -1 Divide each side by '-1'. a = 1 Simplifying a = 1Solution
a = {0, 1}
| X^3+2x^2+3x+6x=0 | | x^2-(3x)-15=3 | | (3n+1)(n-5)=0 | | 49+b^2=41 | | 24=3(a-1)-3(2a+2) | | 4/5z=1-1/5z | | D=4t^2 | | 18x-32=7x+16 | | D=4(16)t^2 | | x^2-5=x+1 | | 9y-14-5y+9=0 | | 7h+14=9n+36-24 | | 3n+4=0 | | 29*11= | | 0.5x=7+12x | | 26+n=48 | | 2x(16x^2-40x+25)-8x^2*(5-4x)=0 | | =-x+4x-2 | | -12x+-18=44 | | -2=-2.5(4)+b | | 2g-20+8g=1-g | | (10^(-1/2))*(10^(5/2)) | | 5x^8=15x^6 | | -2k+2m=m | | 81-(8*11)= | | 5/7.5=7/? | | 16=nm | | x+y=3y-6 | | 81-(811)= | | 5x^2+32x+1=-7x+9 | | -6m=2(3n-1) | | 81-(8*9)= |